A Stable Bifunctional Catalyst for Rechargeable Zinc–Air Batteries: Iron–Cobalt Nanoparticles Embedded in a Nitrogen‐Doped 3D Carbon Matrix. Issue 49 (12th November 2018) - Liu, Xu; Wang, Lei; Yu, Peng; Tian, Chungui; Sun, Fanfei; Ma, Jingyuan; Li, Wei; Fu, Honggang
Abstract: Low‐cost, efficient bifunctional electrocatalysts are needed to mediate the oxygen reduction and oxygen evolution reactions (ORR/OER) in Zn–air batteries. Such catalysts should offer binary active sites and an ability to transfer oxygen‐based species and electrons. A 3D catalyst, composed of nanoparticles of CoFe alloy embedded in N‐doped carbon nanotubes tangled with reduced graphene oxide, was developed, which presents appreciable ORR/OER activity when applied in a Zn–air battery. A high open‐circuit voltage of 1.43 V, a stable discharge voltage of 1.22 V, a high energy efficiency of 60.1 %, and excellent stability after 1 600 cycles at 10 mA cm −2 are demonstrated. An all‐solid‐state battery had an outstanding lifetime and high cell efficiency even upon bending. In situ X‐ray absorption spectroscopy revealed that OOH* and O* intermediates induce variations in the Fe−Fe and Co−Co bond lengths, respectively, suggesting that Fe and Co species are crucial to the ORR/OER processes. Abstract : A bifunctional electrocatalyst for the oxygen reduction and oxygen evolution reactions (ORR/OER) is described. The catalyst consists of alloyed CoFe nanoparticles embedded in a conductive nitrogen‐doped 3D carbon matrix (N‐GCT). Applications in highly stable liquid and all‐solid‐state zinc–air batteries are demonstrated, and the origin of bifunctional electrocatalytic activity revealed.